Decline in Innovation Activity in Fuel and Energy Complex of Russian Federation in 1990s and Its Consequences - E. V. Bodrova; V. V. Kalinov (Научный диалог, 2021)
The relevance of the study is due to the importance of digitalization of the country's fuel and energy complex. On the basis of archival data and a study of the assessments of leading experts, the author considers the problem of the decline in innovative activity in the fuel and energy complex (FEC) of the Russian Federation in the context of liberal reforms implemented in the 1990s. As a result of the analysis of documents, statistical data and other materials, it was proved that investment programs were cur-tailed, drilling in the oil and gas industry was reduced to a minimum, and social problems were growing. Particular attention is paid to identifying the reasons for the decline in innovative activity. The conclusion is made that the crisis situation in the fuel and energy complex, the lack of adequate funding has deprived scientists of the opportunity to develop at a level adequate to the requirements of the modern world energy market. The question is raised about the interaction of the heads of the fuel and energy complex with the central state bodies, which were increasingly complicated due to the increasing tax pressure. It is proved that in the conditions of a general crisis of non-payments, enterprises of the fuel and energy complex, having no free funds, practically stopped provisions to the fund for financing re-search and development work (R&D). The stake on the emergence of “effective managers”, attraction of foreign capital, and a system of unaddressed budgetary support for R&D has not justified itself. Import dependence grew, which has not yet been fully overcome.